Monitoring and prognostic evaluation of patients with congenital hypothyroidism treated in a pediatric endocrinology unit - Ünüvar, Tolga; Demir, Korcan; Abacı, Ayhan; Ataş, Ali; Büyükgebiz, Atilla; Böber, Ece (The Turkish Journal of Pediatrics, 2013)
In this study, the etiological factors, diagnostic approaches, dose, and duration of treatment were compared between cases with transient and permanent congenital hypothyroidism (CH) with respect to prognosis. One hundred and twenty-two patients who received treatments with the diagnosis of CH in the last 10 years were included in the study. The records of the patients were reviewed retrospectively. Serum thyroid- stimulating hormone (TSH) levels at the time of diagnosis were found to be significantly higher, and total thyroxine (TT4) levels were found to be significantly lower in the permanent CH group in comparison to the transient CH group. A statistically significant difference was present between the groups regarding treatment doses, the time needed for TSH decrease to